Technology characteristics that influence adoption of residential distributed energy resources: Adapting Rogers' framework. (September 2022) - Outcault, Sarah; Sanguinetti, Angela; Nelson, Leslie
Abstract: Distributed energy resources (DERs) present an important opportunity to lower the carbon intensity of residential buildings but face numerous barriers to adoption. This paper extends and adapts Rogers' theory of the role of technology characteristics in the diffusion of innovation (Rogers, 1962) to address the unique features of residential DERs. A structured review of the academic and industry literature was conducted to gather data on the technology characteristics that influence residential DER adoption. Careful coding, analysis, and operationalization of the technology characteristics yielded 14 that are relevant, applicable, specific, independent, and distinct from each other. The 14 technology characteristics and logic behind their identification comprise a classification scheme to guide the exploration of how the technology characteristics of residential DERs influence their adoption. Building on that framework, an assessment tool was developed to evaluate technology adoptability, facilitate comparisons across technologies, and identify the specific technology characteristics that pose a challenge for each DER. The framework and the assessment tool can be used by researchers, practitioners, and policymakers to better understand and address the technology characteristics that hinder adoption of residential DERs. Highlights: Rogers' Diffusion of Innovation theory claims technology characteristics influence adoption. Residential distributed energy resources (DERs) have properties not addressed by Rogers. Fourteen technology characteristics that influence residential DER adoption are identified. A tool to evaluate residential energy technology characteristics is presented.